When something is at stake: Differences in soccer performance in 11 vs. 11 during official matches and training games - Olthof, S. B. H.; Frencken, W. G. P.; Lemmink, K. A. P. M. (The Journal of Strength and Conditioning Research, 2019)
11 vs. 11 training games are used to mimic the official match, but differ in playing duration and a consequence of winning or losing. Anxiety levels, crowd pressure, and the intention to win are examples of constraints present in the match, but absent or less prevalent in training. The aim is, therefore, to compare soccer performance in official matches with 11 vs. 11 training games. Six elite youth soccer teams played 5 official matches and 15 training games. Soccer performance, defined as a combination of game characteristics (game duration, transitions, and ball possession duration) and physical (distance covered, high-intensity distance, and sprints), technical (passing), and team tactical performance (inter-team and intra-team distances) and corresponding interaction patterns, was determined with video footage and positional data (local position measurement system). Soccer performance in official matches differed from similar training games, in a way that players covered more distance, sprinted more often, but game pace was lower and players made more mistakes. In addition, team width was smaller and length-per-width ratio larger and teams were tighter coupled in official matches. 11 vs. 11 training games can be used to mimic the match, in particular the team tactical performance. Coaches could increase physical and technical representativeness of training games by raising the stakes and increasing the consequence of winning or losing.